«Positioning theory» e analisi del soggetto lirico (ENTHYMEMA, 2020)
The aim of this paper is to outline a microanalytical method to observe the way in which the lyrical subject builds his own personality by dialoguing with an imaginary or real interlocutor. Referring to positioning theory, I argue that this dialogue can be analyzed as a series of positions, illocutionary acts and plots that the interlocutors continuously generate in the flow of speech, in order to build local micro-identities subjected to a process of continuous negotiation. Then I compare some thesis of positioning theory with the Bakthinian stylistic theory and its application in the essay about Dostoevsky. Finally, I use the tools provided by this method to analyze the poem “Non dite che mi siete indifferenti…” (Voi) by Umberto Fiori.
Keywords: lyrical subject; positioning theory; Bakhtin; Umberto Fiori; Voi